On soliton solutions of Fokas dynamical model via analytical approaches - Badshah, Fazal; Tariq, Kalim U.; İnç, Mustafa; Javed, Rizwan (Springer, 2024)
The nonlinear (4+1)-dimensional Fokas equation (FE) has been demonstrated to be the integrable extension of the Kadomtsev-Petviashvili (KP) and Davey-Stewartson (DS) equations. In nonlinear wave theory, the governing model is one of the fundamental structures that explains the surface waves and interior waves in straits or channels with different depths and widths. In this study, the generalized unified approach, the generalized projective ricatti equation technique, and the new F/G-expansion technique are applied to investigate the higher dimensional nonlinear model analytically. As a result, several solutions are successfully achieved, including dark soliton, periodic type solitons, w-shaped soliton, and single-bell shaped solitons. Along with an explanation of their behavior, we also display a few of the equation's exact solutions graphically. The results demonstrate the effectiveness and simplicity of the approaches mentioned in this article, demonstrating their applicability to a wide range of additional nonlinear evolution issues in numerous scientific and technical disciplines.
Keywords: The generalized unified method; The NFE; The generalized projective ricatti equation technique; The new F/G-expansion technique; Traveling waves solutions; Exact wave solutions